Diversity of Cucurbita moschata Duchesne (loche and cushé) and Cucurbita ficifolia Bouché (chiclayo) in Southern Amazonas, Perú - Gill, Elizabeth R.A.; Ogden, Andrew B.; Oliva Cruz, Segundo Manuel; Guerrero Abad, Juan Carlos (USDA ARS U.S. Vegetable Laboratory, 2024)
The National Institute for Agrarian Innovation (INIA) in Perú, among countless projects, maintains the Peruvian National Cucurbita spp. germplasm bank representing the remarkable Cucurbita spp. diversity in Perú. Prior to this project, the INIA Cucurbita collection covered much of the southern Perú Cucurbita spp. diversity but was lacking Cucurbita spp. samples from northern Perú. Therefore, the Fulbright Program funded this project to investigate and inventory the disappearing diversity of Cucurbita moschata and Cucurbita ficifolia in the Department of Amazonas, Perú. The collection focused on three landraces that belong to two different species (Table 1). The two C. moschata landraces are known in the Amazonas region as loche and cushé, whilst the C. ficifolia landrace is commonly known as chiclayo. Loche has a higher economic value and culinary influence, whilst cushé has a greater phenotypic diversity but is farmed on a smaller scale. All three, loche, cushé and chiclayo, show different physical, culinary, cultural, and geographic adaptations. The objectives of this project included:(a) collecting C. moschata and C. ficifolia samples from different districts in the Department of Amazonas, Perú for seed saving,(b) taking morphological data and photos of each collected sample for analysis, and (c) collecting cultural, historical, and culinary information.